Corneal Topographic Analysis in Patients with Involutional Lower Eyelid Entropion. (17th November 2021) - Yunoki, Tatsuya; Hayashi, Atsushi; Abe, Shinya; Otsuka, Mitsuya
ABSTRACT: Purpose : To analyze the corneal morphology before and after surgery by the advancement of posterior lower eyelid retractors (LERs) alone or in combination with a lateral tarsal strip (LTS) for lower eyelid involutional entropion. Methods: We retrospectively analyzed the cases of 24 consecutive elderly patients (24 eyelids) who underwent posterior layer advancement of LERs alone or in combination with an LTS for involutional entropion. All patients underwent general ophthalmological examinations including best-corrected visual acuity (BCVA), fundus examination, and slit lamp microscopy. The degree of corneal damage was evaluated using the area (A) and density (D) classification of corneal fluorescein staining. Corneal topography was measured using anterior segment optical coherence tomography (AS-OCT). The parameters were steep keratometry (Ks), flat keratometry (Kf), average keratometry (AveK), cylindrical power (CYL), central corneal thickness (CCT), and total higher-order aberrations (HOAs) within a 4-mm diameter. Results: There was no significant difference in the Ks, Kf, AveK, CYL or CCT values between before and after surgery. The HOAs were significantly decreased after surgery. In the AD classification, both the A and D values were significantly decreased after surgery. Significant correlations were observed between preoperative mean HOAs and the mean of A classification, and between preoperative mean HOAs and the mean of D classification. Conclusion: Involutional entropion does not appear to significantly affect corneal morphology before or after posterior LER advancement alone or in combination with an LTS. However, this surgery is thought to result in an improvement of corneal disorders and consequent improvement of HOAs.